Сrisis communications in the information space of wartime Ukraine - Snytko, Olena (Current issues of Ukrainian linguistics: theory and practice, 2023)
The present study explores crisis communications in media space of wartime Ukraine that imply the use of technologies aimed at diagnosing, predicting, and managing crises and, whenever possible, neutralizing their negative consequences. The findings indicate that the identity narrative is the foundation for the ideological matrix of Ukrainian strategic communications during the Russia-Ukraine war. This master narrative outlines the fundamental features and values of the distinctive and unique Ukrainian nation defending its sovereignty and statehood. Not surprisingly, all other pro-Ukrainian narratives draw on this master narrative because the aggressor’s primary goal is to destroy the country’s nationhood and devalue democratic aspirations and pro-European/ pro-Western orientations of its citizens. Crisis communications practices indicate that wartime texts should be short, with balanced factual and emotional parts and a personal message – "Address the whole people and every one of them!" These communication principles have dominated public speeches, including those of the top diplomatic officials, from the start of the third stage of the war. The crisis faced by Ukrainian society during wartime has brought to the forefront a growing number of specific suggestive texts that support the main strategic narratives and boost the morale of citizens – creolized (multimodal) texts that are disseminated through traditional and new media, social networks, combining different information codes (verbal, visual and musical texts). These texts effectively and positively influence Ukrainian society and simultaneously objectify narratives rich in emotional description. The activation of these forms is the result of tension release through creativity. Traditionally used to exert manipulative influence on individuals, this form may prove effective in crisis communication situations due to its propensity to quickly neutralize the state of uncertainty, which is difficult for the psyche.